Basic Helix-Loop-Helix Transcription Factors AabHLH2 and AabHLH3 Function Antagonistically With AaMYC2 and Are Negative Regulators in Artemisinin Biosynthesis - Shen, Qian; Huang, Huayi; Xie, Lihui; Hao, Xiaolong; Kayani, Sadaf-Ilyas; Liu, Hang; Qin, Wei; Chen, Tiantian; Pan, Qifang; Liu, Pin; Tang, Kexuan (Frontiers in Plant Science, 2022)
Plants have evolved sophisticated systems for regulating the biosynthesis of specialized phytochemicals. Artemisinin, which is a sesquiterpene lactone widely used in anti-malaria treatment, is produced by the Artemisia annua L. plant. However, the artemisinin content in A. annua is low and difficult to meet market demands. Studies have shown that artemisinin biosynthesis in A. annua has complex temporal and spatial specificity and is under tightly transcriptional regulation. However, the mechanism of transcriptional regulation of artemisinin biosynthesis remains unclear. In this study, we identified two MYC-type bHLH transcription factors (AabHLH2 and AabHLH3) as novel regulators of artemisinin biosynthesis. These bHLH TFs act as transcription repressors and function redundantly to negatively regulate artemisinin biosynthesis. Furthermore, AabHLH2 and AabHLH3 are nuclear proteins and bind to DNA elements with similar specificity to that of AaMYC2, but lack the conserved activation domain, suggesting that repression is achieved by competition for the same cis-regulatory elements. Together, our findings reveal a novel artemisinin biosynthesis regulatory network and provide new insight into how specialized metabolites are modulated in plants, and propose a model in which different bHLH TFs coordinated regulation artemisinin production in the plant. Finally, this study provides some useful target genes for metabolic engineering of artemisinin production via CRISPR/Cas9 gene editing.